Geochemistry of hydrothermally altered rocks with gold mineralization hosted in alkaline complex in Hongshan area, Taihang Orogen, North China. (8th February 2016) - Zhang, Jingsen; Zhang, Jing; Zhai, Yanchao
Abstract : Purpose: This paper aims to elucidate the geochemical characteristics of the hydrothermally altered rocks with gold mineralization and the elemental transfers in hydrothermal alteration hosted in alkaline complex in Hongshan area, Taihang Orogen, North China, and preliminarily discuss the relationship between the gold mineralization and the hydrothermal alteration. Design/methodology/approach: Based on detailed field investigation, sampling and petrographical observation, major oxides and trace elements of nine rock samples are analyzed, and the method of mass balance equation is used in calculation of the elemental transfer. Findings: Three alteration stages in the Hongshan area are identified, which are the early, main and late alterations. The early one is characteristic of extensive pyritization in the complex, which is related to the mantle-derived magmas and occurs before gold mineralization. The main one is characterized by developing a great deal of altered rock in fracture zones with the gain of many elements and the loss of a few elements. The late one is dominated by limonitization, that is limonite replacing the early pyrite or Fe2 O3 replacing FeO in rocks. In the main alteration, the altered rocks obviously gain fluid component (LOI, i.e. loss on ignition) and elements such as V, As, Rb, Au, La, Ce and Nd and total rare earth elements (REEs). Elements such as K, Fe, Cu, Zn, Y, Mo, Sb, W, Re and U are gained in some altered rocks. Na and Sr are lost in all altered rocks, and Th and Bi are lost in some ones in the meantime. The following elements: Si, Mg, Mn, Ca, Li, Sc, Cr, Co, Ni, Zr, Ag, Ba and Hg show either gain or loss in different altered rocks. Au is notably enriched in the hydrothermal alteration. The elemental gain or loss in the altered rocks indicates that the main mineralization develops extensive de-alkalinization, local potassic metasomatism, silicification or desilicification.